2022
DOI: 10.3389/fimmu.2022.1009634
|View full text |Cite
|
Sign up to set email alerts
|

The established chemokine-related prognostic gene signature in prostate cancer: Implications for anti-androgen and immunotherapies

Abstract: BackgroundProstate cancer (PCa) was one of the most common malignancies among men, while the prognosis for PCa patients was poor, especially for patients with recurrent and advanced diseases.Materials and methodsFive PCa cohorts were downloaded from The Cancer Genome Atlas and Gene Expression Omnibus databases, and the biochemical recurrence (BCR)-related chemokine genes were identified by LASSO-Cox regression. The chemokine-related prognostic gene signature (CRPGS) was established, and its association with PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Transcriptomic data and survival information for 140 patients with PRAD were downloaded from the Memorial Sloan Kettering Cancer Centre project (MSKCC) using cBioPortal ( http://www.cbioportal.org/ ). We obtained the GSE70768 dataset from the NCBI GEO ( http://www.ncbi.nlm.nih.gov/geo ) public database [ 21 ]. This dataset contained data from 111 patients with PRAD, including their complete expression profiles and survival information.…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptomic data and survival information for 140 patients with PRAD were downloaded from the Memorial Sloan Kettering Cancer Centre project (MSKCC) using cBioPortal ( http://www.cbioportal.org/ ). We obtained the GSE70768 dataset from the NCBI GEO ( http://www.ncbi.nlm.nih.gov/geo ) public database [ 21 ]. This dataset contained data from 111 patients with PRAD, including their complete expression profiles and survival information.…”
Section: Methodsmentioning
confidence: 99%
“…PCa purity and CD4 + T cells, CD8 + T cells, B, macrophage, dendritic, and neutrophil infiltration were associated with CXCL14 expression. The researchers additionally discovered that PCa pathology T stage and immunological score were significantly correlated with CXCL14 expression [ 221 ]. An earlier study found that CXCL14-expressing CAF and fibroblasts stimulated by CXCL14 upregulate NOS1.…”
Section: Chemokines/cxcrs and Pcamentioning
confidence: 99%
“…Transcriptomic data and survival information for 140 patients with PRAD were downloaded from the Memorial Sloan Kettering Cancer Centre project (MSKCC) using cBioPortal (http://www.cbioportal.org/). We obtained the GSE70768 dataset from the NCBI GEO (http://www.ncbi.nlm.nih.gov/geo) public database [21]. This dataset contained data from 111 patients with PRAD, including their complete expression pro les and survival information.…”
Section: Data Acquisition and Preprocessingmentioning
confidence: 99%